STUDI KELAYAKAN USAHA MIKRO KECIL DAN MENENGAH DESA BANDUNG KECAMATAN PECALUNGAN (Lembaga Pengembangan Kinerja Dosen, 2021)
Chicken noodles are one of the micro, small and medium enterprises in Batang Regency, Pak Daryoto's chicken noodles are one of the chicken noodle traders who sell or hang out in front of the Nurul Hikmah mosque, Bandung Village, Pecalungan District, Batang Regency, this chicken noodle has been around since 2013 and still survives today. The price offered by Moro Seneng chicken noodles is very affordable, making Moro Seneng chicken noodles popular with all circles, the purpose of this study was to determine the feasibility of Moro Seneng chicken noodle business based on market and marketing aspects, technical aspects, human resource aspects and financial aspects. This research uses qualitative methods used to describe non-financial aspects, namely legal aspects, technical and technological aspects, market and marketing aspects, human resource aspects, management aspects and economic aspects. The results of this study state that after analyzing the aspects of a business feasibility study from legal, human resources, management, technical and technological, marketing and financial aspects, the results show that this business is feasible to run. By utilizing technological developments, Moro Seneng Chicken Noodle uses Facebook media to conduct promotions and can deliver messages with WhatsApp media. That way Moro Seneng chicken noodle has a wide market share not only within the scope of the village. Market and marketing analysis shows that the prospects for the chicken noodle business are very good, this can be seen from the increase in demand every year. The price is affordable, and the strategy related to the marketing mix is very good.